REVITALISASI EKONOMI UNTUK MENINGKATKAN PRODUKTIVITAS, NILAI TAMBAH DAN AKSES PASAR BERBASIS KELESTARIAN KAWASAN HUTAN LINDUNG â€œBUKIT DAUNâ€ DI KABUPATEN REJANG LEBONG - Sungkono, Sungkono; Sari, Anggri Puspita (JURNAL EKOMBIS REVIEW, 2015)
Soengkono, Anggri Puspita Sari; This study aims to revitalize the local economy based on the economic potential of resources and preservation of protected areas through appropriate integrated technological innovation to improve productivity, value and sustainable market access added. Data analysis was performed in conjunction with the data collection process (analysis will) and applicable techniques in qualitative penelitihan. Appropriate development model used technologies adapted, arranged with the potential of existing human resources, natural resources, the existence of potential team of experts, as well as the potential of the existing business environment. Development of models aimed at the formation of community groups productive coffee farmers, the development of appropriate production technology modules coffee processing and packaging printing business. Community groups are directed to the production of coffee processing business establishment and packaging printing business through structured training activities, the establishment of business units, business management, training and coaching development efforts.Key words: Revitalization, Economic, Technology, Productivity, Sustainability